2005
DOI: 10.1242/jcs.01613
|View full text |Cite
|
Sign up to set email alerts
|

Elastin-derived peptides enhance angiogenesis by promoting endothelial cell migration and tubulogenesis through upregulation of MT1-MMP

Abstract: Elastin-derived peptides display a wide range of biological activities in a number of normal and transformed cells but their involvement in angiogenesis has not been reported. In the present study, we show that κ-elastin and VGVAPG hexapeptide elastin motif accelerated angiogenesis in the chick chorio-allantoic membrane in an in vivo model. They also stimulated pseudotube formation from human vascular and microvascular endothelial cells in the matrigel and collagen models as well as cell migration in an in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
172
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(185 citation statements)
references
References 87 publications
(90 reference statements)
7
172
0
4
Order By: Relevance
“…One of our main focuses was to refine the commonly used scratch or wound healing assay into a highly quantitative Super Scratch assay. The scratch assay before this work had not progressed beyond a single or few timepoint assay where measurements were made of distance between edges (Maschler et al 2005;Zhu et al 2004;Pratt et al 2005;Wadham et al 2003;Besson et al 2004;Cretu et al 2005;Hoang et al 2004;John et al 2004;Ray et al 2003;Lynch et al 2005;Yarrow et al 2004), number of cells entering a defined area (Petridis et al 2004;Nishio et al 2005;Zhu et al 2004;Piccolo et al 2002;Robinet et al 2005;Raftopoulou et al 2004;Zhu et al 2005), or qualitative assessment without quantitation (Gavert et al 2005;Yoshida et al 2004;Zhang et al 2005;Herren et al 2001;Lee et al 2004;Motegi et al 2003;Laurent-Matha et al 2005;Miao et al 2005). We have shown that such a method of analysis is not as accurate a representation of cell migration as tracking individual cells starting from the advancing front of the wound.…”
Section: Discussionmentioning
confidence: 98%
“…One of our main focuses was to refine the commonly used scratch or wound healing assay into a highly quantitative Super Scratch assay. The scratch assay before this work had not progressed beyond a single or few timepoint assay where measurements were made of distance between edges (Maschler et al 2005;Zhu et al 2004;Pratt et al 2005;Wadham et al 2003;Besson et al 2004;Cretu et al 2005;Hoang et al 2004;John et al 2004;Ray et al 2003;Lynch et al 2005;Yarrow et al 2004), number of cells entering a defined area (Petridis et al 2004;Nishio et al 2005;Zhu et al 2004;Piccolo et al 2002;Robinet et al 2005;Raftopoulou et al 2004;Zhu et al 2005), or qualitative assessment without quantitation (Gavert et al 2005;Yoshida et al 2004;Zhang et al 2005;Herren et al 2001;Lee et al 2004;Motegi et al 2003;Laurent-Matha et al 2005;Miao et al 2005). We have shown that such a method of analysis is not as accurate a representation of cell migration as tracking individual cells starting from the advancing front of the wound.…”
Section: Discussionmentioning
confidence: 98%
“…Angiogenesis resulting from injury stimulus plays a key role in repairing the infarcted heart by expanding the existing vascular network. Previous study demonstrated that EGCG, a general inhibitor of MMPs, [24] inhibits angiogenesis [25]. However, the molecular mechanisms by which EGCG inhibits angiogenesis are still unclear; thus, MSC MP9 -129SvEv mice employed for this study further demonstrated the important role of MMP-9 in angiogenesis.…”
Section: Msc Cx4 Release Anti-fibrotic Enzymesmentioning
confidence: 80%
“…generate elastin fragments i.e. elastokines with potent angiogenic activity (Robinet et al, 2005). At the opposite, proteolysis of plasminogen and  3 chain of collagen IV leads to the formation of angiostatin and tumstatin (Cornelius et al, 1998;Kessenbrock et al, 2010).…”
Section: Resultsmentioning
confidence: 99%